2009
DOI: 10.4103/0970-4388.57097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of caries experience in 3-6-year-old children, and dental attitudes amongst the caregivers in the Ludhiana city

Abstract: Early Childhood Caries (ECC) is a lifestyle disease that begins when the child's teeth erupt in the oral cavity. The distinctive pattern of decay rapidly spreads from one tooth to another and involves the surfaces of teeth that are usually not at risk. Detection of disease is crucial to control the oral condition using preventive and therapeutic regimes. The aim of this study was to determine the prevalence of caries in children of age 3-6 years in Ludhiana and to examine the relationship between age and carie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 19 publications
5
17
0
2
Order By: Relevance
“…[121314151617] In the Middle East, the prevalence of ECC has been reported to be between 22% and 61% and in Africa, between 38% and 45%. [18192021] In India, a prevalence rate of 44% has been reported,[22] with a study reporting a prevalence of 52.87%,[23] and 54.1% in the preschool children of Hubli and Dharwad. [24]…”
Section: Introductionmentioning
confidence: 99%
“…[121314151617] In the Middle East, the prevalence of ECC has been reported to be between 22% and 61% and in Africa, between 38% and 45%. [18192021] In India, a prevalence rate of 44% has been reported,[22] with a study reporting a prevalence of 52.87%,[23] and 54.1% in the preschool children of Hubli and Dharwad. [24]…”
Section: Introductionmentioning
confidence: 99%
“…[3,8] Prevalence of dental caries is approximately 60% all around the world [20]. In previous studies prevalence of ECC in India is approximately 51% and 54.1% respectively [16,17]. Available data on dental caries reveal that Pakistan has been classified as a low caries country, on the positive side 50% of the children between the ages of 12-15 years are caries free and on the negative side 97% of all carious lesions remained untreated [13,19].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several papers in the past decade that have shown that the lack of maternal education has been one of the key reasons for the spread of ECC. [20212223] This risk when combined with geographic and socioeconomic barriers to health-care results in clearly observable deterioration of oral health and increased rates of ECC. [2425262728]…”
Section: Introductionmentioning
confidence: 99%